2020
DOI: 10.2196/15607
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Media to Increase the Impact of Health Research: Systematic Review

Abstract: Background Academics in all disciplines increasingly use social media to share their publications on the internet, reaching out to different audiences. In the last few years, specific indicators of social media impact have been developed (eg, Altmetrics), to complement traditional bibliometric indicators (eg, citation count and h-index). In health research, it is unclear whether social media impact also translates into research impact. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 78 publications
(261 reference statements)
1
57
0
Order By: Relevance
“…Data from Pew Research Center have shown that internet use for racial and ethnic minorities is comparable to non-Hispanic whites [ 2 ]. As a result, health dissemination has become more streamlined, and use of the internet has become a popular tool for fostering complex conversations, increasing access to health information, and improving medical outcomes [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. For example, systematic reviews of digital health interventions have found clinical benefits among individuals with musculoskeletal conditions and improved quality of life and mental health outcomes for cancer patients [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data from Pew Research Center have shown that internet use for racial and ethnic minorities is comparable to non-Hispanic whites [ 2 ]. As a result, health dissemination has become more streamlined, and use of the internet has become a popular tool for fostering complex conversations, increasing access to health information, and improving medical outcomes [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. For example, systematic reviews of digital health interventions have found clinical benefits among individuals with musculoskeletal conditions and improved quality of life and mental health outcomes for cancer patients [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, utilization of social media channels was the only feasible survey option during the COVID-19 pandemic. The rise in social media use during this pandemic may result in timely identification and promotion of publications vis-a-vis conventional metrics that may delay impact on education, research, and practice [25].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers with access to altmetric.com and other social media aggregators may enrich their research and reviews with a new dimension of empirical evidence which is largely based on tweets, Facebook mentions, and other public sharing and commenting activities [21]. Journal editors may employ altmetric analyses for evaluating the efficiency of post-publication promotion and, to some extent, prediction of citation metrics [22].…”
Section: Complementary Use Of Altmetric Analysesmentioning
confidence: 99%